Collective Complaints as a Means for Protecting Social Rights in Europe - Palmisano, Giuseppe (Anthem Press, 2022)
This monograph explores and clarifies the specific features of the collective complaints procedure, established by the treaty system of the European Social Charter as an instrument for the protection of social rights, in the light of its evolutive application by the European Committee of Social Rights.